2016
DOI: 10.5152/ucd.2015.2913
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of fine needle aspiration biopsy of axillary lymph nodes in preoperative breast cancer staging

Abstract: , 46 women were prospectively enrolled in the study. Ultrasound guided-FNABs for axillary assessment were performed preoperatively. Cytology results were compared with histopathology reports to determine its sensitivity, specificity, negative and positive predictive value and accuracy.Results: Nineteen cases that had malignant cytology on FNAB also had axillary involvement in axillary lymph node dissection (ALND) without any false-positive results. The sensitivity and specificity of US-guided FNAB were 63.3% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
(35 reference statements)
3
8
1
Order By: Relevance
“…18,20 According to them, false-positives are mostly due to cytologic misinterpretation of cells. Conversely, recent studies reported the absence of false-positive results, [9][10][11][12][13][14] and no false-positives results from FNAC were obtained in this present study.…”
Section: Resultscontrasting
confidence: 86%
See 3 more Smart Citations
“…18,20 According to them, false-positives are mostly due to cytologic misinterpretation of cells. Conversely, recent studies reported the absence of false-positive results, [9][10][11][12][13][14] and no false-positives results from FNAC were obtained in this present study.…”
Section: Resultscontrasting
confidence: 86%
“…Other reasons for false-negative FNAC results may be sampling error, 12 and overdiagnosis with US. 13 A recent study reported that LNs < 1.2 cm in size appeared to have a significantly higher falsenegative percentage than larger LNs. 19 Ewing et al also reported that a relationship existed between the percentage of LNs replaced by carcinoma and false-negative cytology.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…If tumor cells are identified during US-FNAC or CNB, diagnosis is confirmed as metastatic ALNs. However, when the results of US-FNAC or CNB are negative, the possibility of a false negative by sampling error or overdiagnosis of AUS should be considered [ 78 , 79 ]. Because of these cases, the sensitivity can be lowered.…”
Section: Discussionmentioning
confidence: 99%